Ulcerations of different etiology. Three case studies - Mościcka, Paulina; Szewczyk, Maria T.; Cwajda-Białasik, Justyna; Hancke, Elżbieta; Jawień, Arkadiusz; Brazis, Paweł (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2012)
The paper presents three cases of chronic wounds, associated with traumatic ulceration of the foot region, recurrent venous ulceration, and iatrogenic ulceration resulting from the extravasation of the chemotherapeutic agent. The diagnoses are discussed along with the objectives of nursing care. In all the cases, therapeutic and nursing activities were aimed at the cleaning of the wound bed, optimization of the systemic and local conditions of healing, reduction of the wound area, its complete healing, and improvement of the patient’s comfort (e.g. alleviating wound-associated pain). These activities were reflected by the reduced area of wounds and their healing.